Phase Evolution of M2 High Speed Steel During Selective Laser Melting: Experimental Investigation and Modelling - Liu, Zhong Hong (2016)
This work studies the phase evolution in SLM where the resultant melt is considered as a moving volumetric heat source modeled as a double ellipsoidal heat source. The cooling rates and temperatures at different locations along the substrate and away from the heat source during the SLM process were simulated with the MATLAB program. Thermal gradient graphs were generated and the range of HAZ was identified from the corresponding theoretical austenitising temperature of M2 HSS. The associated HAZs were examined from their melt cross sections and validated with the simulated results. The evaluated HAZs from the experiments were found to be very close to the simulated HAZ range. The development of this model also provides the temperature distribution and cooling profiles in SLM.